Genetic mouse models to study pancreatic cancer-induced pain and reduction in well-being - Hirth, Michael; Xie, Yong; Höper, Christiane; Prats, Amandine; Hackert, Thilo; Ebert, Matthias; Kuner, Rohini (Cells, 2022)
In addition to the poor prognosis, excruciating abdominal pain is a major challenge in pancreatic cancer. Neurotropism appears to be the underlying mechanism leading to neuronal invasion. However, there is a lack of animal models suitable for translationally bridging in vitro findings with clinical trials. We characterized KPC (KrasG12D/+; Trp53R172H/+; P48-Cre) and KPPC (KrasG12D/+; Trp53R172H/R172H; P48-Cre) mice with genetically determined pancreatic ductal adenocarcinoma (PDAC) and compared them with an orthotopic pancreatic cancer mouse model, healthy littermates and human tissue. We analyzed behavioral correlates of cancer-associated pain and well-being, and studied neuronal remodeling and cytokine expression. Histologically, we found similarities between KPC and KPPC tissue with human samples. Compared to healthy littermates, we detect nerve fiber hypertrophy, which was not restricted to a certain fiber type. Interestingly, while KPPC mice showed significantly reduced well-being, KPC mice emerged to be better suited for studying long-lasting cancer pain that emerges over a slow course of tumor progression. To address the neuroinflammatory correlate of loss of well-being, we studied cytokine levels in KPPC mice and observed a significant upregulation of CXCL16, TNFRSF5, CCL24, CXCL1, CCL22, CLL20 and CX2CL1. In summary, we demonstrate that the KPC mouse model is best suited to studying cancer pain, whereas the KPPC model can be employed to study cancer-associated reduction in well-being.